"Fat People Exercise Too!": Perceptions and Realities of Shopping for Women's Plus-Size Exercise Apparel. (April 2020) - Greenleaf, Christy; Hauff, Caitlyn; Klos, Lori; Serafin, Gabriel
Women, regardless of size, should have access to functional, fashionable, and affordable exercise apparel. Grounded in Lamb and Kallal's Functional, Expressive, and Aesthetic Consumer Needs Model, we explored (a) women's perceptions of plus-size exercise apparel and shopping experiences and (b) plus-size exercise apparel at online retailers. In Study 1, women reported their shopping behaviors, satisfaction, affect, and feedback for designer and retailers. In Study 2, availability, cost, and color variety of plus-size exercise T-shirts were documented at online retailers. Images of product models and sizing chart variations were examined. Women were generally dissatisfied with apparel-related functionality, fashionability, and cost. Plus-size exercise T-shirts at online retailers were limited in color variety and size availability and cost more than straight-size apparel. Unrealistic models and wide sizing variations appear problematic. Advocacy and action are needed to provide women with larger bodies' equitable access to functional, expressive, aesthetic, and affordable exercise apparel.